Acta Universitatis Danubius. Œconomica, Vol. 14, No. 2 - part 3: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
The article analizes the main economic indicators of the World for each of the developing countries or regions of the world. A number of indicators are analyzed, such as: Expenses, Exports of goods and services, Imports of goods and services, GDP, Gross capital formation, Inflation, consumer prices, Revenue, excluding grants.